2018
DOI: 10.1111/1365-2664.13283
|View full text |Cite
|
Sign up to set email alerts
|

Landscape structure regulates pest control provided by ants in sun coffee farms

Abstract: 1. Ants play a fundamental role in coffee pest control. Despite this, there is a lack of understanding about how landscape configuration and composition regulate the ecosystem service provided by ants in sun coffee farms within highly fragmented landscapes.2. We measured whether landscape structure influences ants' ability to regulate coffee berry borer (CBB) in sun coffee farms in Southeastern Brazil. Considering the ecological interactions between ants and CBB at three different stages of pest control (reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 51 publications
2
42
1
Order By: Relevance
“…For natural enemies that rely only on resources within farm fields, proximity to seminatural habitats can be irrelevant [40] or even detrimental. For example, pests in sun-grown Brazilian coffee were suppressed by ants adapted to open habitats and, in this case, pest suppression increased at greater distances from forest fragments [41]. Similarly, some parasitoids overwinter in oilseed rape fields, and were more abundant and effective when fields were isolated from forests [42].…”
Section: Connectivitymentioning
confidence: 96%
See 1 more Smart Citation
“…For natural enemies that rely only on resources within farm fields, proximity to seminatural habitats can be irrelevant [40] or even detrimental. For example, pests in sun-grown Brazilian coffee were suppressed by ants adapted to open habitats and, in this case, pest suppression increased at greater distances from forest fragments [41]. Similarly, some parasitoids overwinter in oilseed rape fields, and were more abundant and effective when fields were isolated from forests [42].…”
Section: Connectivitymentioning
confidence: 96%
“…For example, we note that, while six studies documented correlations between natural enemy and pest density (arrow i), without an experimental approach, the relative strengths of landscape predictors and numeric responses between enemies and prey are unknown. Based on [37][38][39][40][41][42][43][44][45]51,74]. millennia, and change relatively slowly.…”
Section: Figure 2 Viewing Pest Suppression Through the Lens Of Multimentioning
confidence: 99%
“…In an artificial predator community with three ant species, pest suppression was higher than in a community with only one predator ant species; additionally, pest diversity reduced the efficiency of a single predator species at suppressing pest damage but did not limit multiple‐predator communities (Gonthier, Kuesel & Perfecto, 2015). Ants reduced damage caused by coffee pests in landscapes with high forest cover within a 2 km radius, where biodiversity is higher (Aristizábal & Metzger, 2019). Also in coffee farms, the fruit set increases with the diversity of pollinating bees, and this diversity is mediated by the distance to tropical forest (Klein et al ., 2002).…”
Section: Interaction Of Services Provided By Social Insects With Envimentioning
confidence: 99%
“…The effects of landscape structure and crop management on insects and associated services and disservices have been widely investigated in temperate regions at multiple spatial scales. However, this relationship is understudied in Brazilian agricultural landscapes, where only a handful of recent studies have been reported (Sartuni et al 2016;Librán-Embid et al 2017;Hipólito et al 2018;Aristizábal and Metzger 2018). Assessments in the Neotropics often rely on temperate data even though the effects of landscape elements and crop management on insects may differ between regions.…”
Section: Introductionmentioning
confidence: 99%